Gut Microbiota Profile in Pediatric Patients With Inflammatory Bowel Disease: A Systematic Review - Zhuang, Xiaojun; Liu, Caiguang; Zhan, Shukai; Tian, Zhenyi; Li, Na; Mao, Ren; Zeng, Zhirong; Chen, Minhu (Frontiers in Pediatrics, 2021)
Accumulating evidence have implicated gut microbiota alterations in paediatric and adult patients with inflammatory bowel disease (IBD); however, the results of different studies are often inconsistent and even contradictory. It is believed that early changes in new-onset and treatment-naïve paediatric patients are more informative. We performed a systematic review to investigate the gut microbiota profiles in paediatric IBD and identify specific microbiota biomarkers associated with this disorder. A total of 41 original studies investigating gut microbiota profiles in paediatric patients with IBD were included in this review. Several studies have reported a decrease in α-diversity and an overall difference in β-diversity of gut microbiota. Although no specific gut microbiota alterations were consistently reported, a gain in Enterococcus and a significant decrease in Anaerostipes, Blautia, Coprococcus, Faecalibacterium, Roseburia, Ruminococcus, and Lachnospira were found in the majority of the included articles. Such altered trend could also be observed in adult patients with IBD, indicating their crucial role in the pathogenesis of this disease. Moreover, there is insufficient data to show specific microbiota bacteria associated with disease activity, location, and complications in paediatric IBD. This systematic review identified evidence for differences in the abundance of some bacteria in paediatric patients with IBD when compared to patients without IBD; however, no clear overall conclusion could be drawn from the included studies due to inconsistent results and heterogeneous methodologies. Further studies with large samples that follow more rigorous and standardized methodologies are needed.